“Somos Amazonía,” a New Inter-indigenous Identity in the Ecuadorian Amazonia: Beyond a Tacit jus aplidia of Ecological Origin? - Saqalli, Mehdi; Béguet, Eva; Maestripieri, Nicolas; de Garine, Eric (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The double colonization of the Northern Ecuadorian Amazon, coming from the Southern Amazon but mainly from the Coast and Sierra, has multiplied perceptions, rights, and management methods in this territory. This article explores these differences and reconstructs the history of this colonization and the rights of access to land, which are private for the colonos (settlers) and mostly communal for the indígenas (indigenous people). These legally differentiated groups are similar in their perception of the territory and their socioeconomic and environmental limitations: most agricultural products are not profitable. Between thegrowing metropolises and the remaining forest, the countryside is slowly shrinking. Communities are appearing that combine indigenous people and settlers and that copy the indigenous communities’ rights and practices. However, this communal right is acquired for the Amazonian groups but not for others, indígenas or colonos, defining de facto a jus aplidia, along with jus soli and jus sanguinis.